2013
DOI: 10.1242/jeb.089961
|View full text |Cite
|
Sign up to set email alerts
|

Launches, squiggles and pounces, oh my! The water–land transition in mangrove rivulus (Kryptolebias marmoratus)

Abstract: SUMMARYMangrove rivulus (Kryptolebias marmoratus) are small fusiform teleosts (Cyprinodontiformes) with the ability to locomote on land, despite lacking apparent morphological adaptations for terrestrial movement. Rivulus will leave their aquatic habitat for moist, terrestrial environments when water conditions are poor, or, as we show here, to capture terrestrial insects. Specimens were conditioned to eat pinhead crickets on one side of their aquaria. After 2weeks of conditioning, a barrier with a slope of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Matthes, 1977;Lowry et al, 2005;Pronko et al, 2013). For feeding strikes in general, Weihs (1973) surmised that when a fish was sufficiently motivated by hunger, efficiency was secondary to short-term energy use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matthes, 1977;Lowry et al, 2005;Pronko et al, 2013). For feeding strikes in general, Weihs (1973) surmised that when a fish was sufficiently motivated by hunger, efficiency was secondary to short-term energy use.…”
Section: Introductionmentioning
confidence: 99%
“…The African tetras Brycinus nurse and Alestes baremoze can jump up to 1 m into the air to dislodge seeds from rice plants and then eat the seeds after they have fallen into the water (Matthes, 1977). The mangrove rivulus (Kryptolebias marmoratus) uses multiple kinematic modes, including jumping S-type 'launches', to travel up banks to feed on land (Pronko et al, 2013). Lowry et al (2005) revealed silver arawana (Osteoglossum bicirrhosum) jump using Sstarts similar to those executed by ambush predators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental variables may combine with motor pattern plasticity to generate distinct behaviors; gravitational loads, buoyancy, viscosity and other environmental mechanics may lead to performance differences, or multifunctionality, in water and land (Nishikawa et al, 2007;Denny, 1993;Vogel, 1994). Many animals are capable of multifunctionality, such as turtles using their appendages to paddle and walk (Earhart and Stein, 2000), eels undulating their bodies for swimming in water and moving onto land (Gillis, 1998(Gillis, , 2000Biewener and Gillis, 1999;Ellerby et al, 2001), the Pacific leaping blenny using its median and paired fins to swim in water and for hopping and twisting on land (Hsieh, 2010), and the mangrove rivulus using its body for transitioning onto land (Pronko et al, 2013) and tail-flipping once out of the water (Gibb et al, 2013;Ashley-Ross et al, 2014). Nishikawa and colleagues (2007) hypothesized that the environment may be an important factor in causing neural circuits to reorganize, making it difficult to tease apart the 'collective output' involving the relationships between the brain, sensory organs, muscles and the environment in terms of the evolution of a novel muscle pattern or behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The mangrove rivulus, Kryptolebias marmoratus Poey 1880 (Cyprinodontiformes), is an amphibious fish that makes temporary excursions onto land for various reasons: actively pursuing prey at the water-land interface, purposefully leaving the water as a result of poor conditions such as high levels of hydrogen sulfide or anoxia, being stranded at low tide or escaping an aquatic predator (Abel et al, 1987;Regan et al, 2011;Pronko et al, 2013). Minnows, gobies, sculpins and some other groups of teleost fishes are also capable of finding themselves on land through active and passive means (Gibb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Harris, 1960;Ellerby et al, 2001;Swanson and Gibb, 2004;Sayer, 2005;Gibb et al, 2011;Ashley-Ross et al, 2013;Pronko et al, 2013;Close et al, 2014;Pace and Gibb, 2014;Standen et al, 2014;Bressman et al, 2015;Flammang et al, 2016). One strategy is to rely on fixed adaptations that are a compromise for movement in air and water.…”
Section: Buoyancy Gravity and Movement On Landmentioning
confidence: 99%